Cooperative Strategy for Airline Code-Share Agreements – A Comparative Analysis - TENG, Lan; TANG, Mincong (Promet - Traffic&Transportation, 2024)
Members of marketing airline alliances cooperatively book seats from the operating airline and compete with each other in the market. This paper models and discusses two types of bargaining pricing processes: representative-based and agent-based cooperative bargaining. It also considers the internal negotiation mechanism within the marketing airline alliance for representative-based bargaining. Using a cooperative bargaining approach, the effects of marketing airline mergers in code-share agreements with the operating airline are analysed. The performance of two sub-strategies under representative-based bargaining is compared with the non-cooperative case. The study concludes that representative-based bargaining without internal negotiation intensifies competition, while representative-based bargaining with internal negotiation has the opposite effect. Cooperative bargaining with internal negotiation benefits both the marketing airlines and the operating airline, whereas representative-based bargaining without internal negotiation may result in a total profit loss. The choice of which bargaining strategy to adopt depends on the bargaining power and the substitutability of different market airline brands. This research provides the basis and support for the formulation of pricing strategies in airline alliances’ code-sharing.